Determining the Height of Water-Flowing Fractured Zone in Bedrock-Soil Layer in a Jurassic Coalfield in Northern Shaanxi, China. (21st October 2021) - Feng, Jie; Wang, Sujian; Hou, Enke; Ding, Xiang; Duan, Huijun
Abstract : The height of the water-flowing fractured zone is the most important technical parameter for water prevention and control in a coal mine. Due to the numerous factors affecting the water-flowing fractured zone, it is difficult to accurately identify the zone. Currently, no effective way exists for determination of the water-flowing fractured zone in a soil layer. To accurately determine the development law of the water-flowing fractured zone in the bedrock-soil layer of a Jurassic coalfield in northern Shaanxi, China, we conducted a comprehensive study using microresistivity scanning imaging technology, apparent density logging, long-range gamma logging, observation on drilling flushing fluid consumption, physical simulation, and numerical simulation. The following results were obtained: (1) The ratio of the height of the water-flowing fractured zone to the mining height was 28.3–28.5, which was obtained by microresistivity scanning imaging technology, whereas the ratio of the height of the water-flowing fractured zone to the mining height was 28.1–29.1, determined by apparent density logging, long-range gamma logging, physical simulation, and numerical simulation. The microresistivity scanning imaging results were consistent with those obtained by other methods. (2) Based on the thickness of the soil layer and the bedrock, the height model of the water-flowing fracture zone was divided into four regions, that is, the thick bedrock-thick soil layer region, thick bedrock-thin soil layer region, thin bedrock-thin soil layer region, and thin bedrock-thick soil layer region. A mathematical model describing the difference between the thickness of the water-flowing fractured zone and the bedrock and the thickness of the soil under the condition of bedrock-soil was established. (3) We conclude that microresistivity scanning imaging technology can accurately detect the height of the water-flowing fractured zone in a soil layer, and the apparent density logging and long-range gamma logging can precisely detect the height of the water-flowing fractured zone in bedrock. This is a new comprehensive method for research on the height of the water-flowing fractured zone that can provide a reliable basis for water prevention and control in mines.